Technology and the World the Slaves Made - Gudmestad, Robert H. (History compass, 2006)
The study of American slavery is a crowded field and each year the historical profession witnesses the publication of several new books. Despite this steady onslaught of scholarship, significant gaps remain in our understanding of slavery and its influence on the South. One area that has lacked sustained attention is the nexus of slavery and technological development. Several new books demonstrate that changes in technology profoundly altered the lives and labor of slaves. Historians have approached the presence of technology in a slave society from several different traditions. Some scholars argued that plantation development and mechanical progress were difficult to wed together, while others noted the progressive nature of southern agricultural production, but discussions of white attitudes and behavior overshadowed the effects of machinery on the lives of slaves. An innovative approach has emphasized the employment of slaves in factories, but such works have done little to provide insight into how technological innovation influenced plantation slaves. Several new studies have reversed these trends and promise to lead us in important directions. Examinations of the cotton gin, steamboats, sugar plantations, and clocks have revealed that technology brought enormous change to the bulk of slaves, not just those living in urban areas or working in factories. Patterns and practices of work, opportunities for autonomy, and time away from the master's unstinting gaze, all changed because of mechanical innovation. Taken together, these new works also provide clues to the making and remaking of the southern economy and society.